Estimation of surface formaldehyde (HCHO) concentrations and HCHO-related cancer risk in a pair of agricultural zones situated in southern Mexico through the Ozone Monitoring Instrument - Cristina A. Mendoza-Rodríguez; Claudia Rivera Cárdenas; Carlos Espinosa-Ponce (Environmental Pollution and Management)
In humans, formaldehyde (HCHO) has been linked to nasopharyngeal cancer (NPC), but continuous surface HCHO measurements are scarce, limiting the estimates of the risk of NPC related with inhalation of environmental HCHO. Therefore, in this work we employed OMI HCHO columns between January 2005 and December 2016, as well as ancillary data, to estimate surface concentrations of HCHO and with these, HCHO-related cancer risk estimates in two zones (Oax and Chis) situated in southern Mexico. Annually averaged surface concentrations ranged from 0.94 μg m−3 to 1.89 μg m−3 in Oax, as well as between 1.07 μg m−3 and 1.91 μg m−3 in Chis. Annually averaged surface concentrations showed a statistically significant (p < 0.05) increasing trend in Oax, which was partially attributed to the increase of isoprene emissions in the zone (p < 0.05). We used the Inhalation Unit Risk (IUR) from two different agencies to estimate HCHO-related cancer risk in each studied zone. Annual HCHO-related cancer risk ranged from 5.66 × 10−6 to 2.08 × 10−5 in Oax, and from 6.40 × 10−6 to 2.10 × 10−5 in Chis. Considering these ranges, people in Oax and Chis are at possible-probable lifetime risk of getting NPC as a result of continuous inhalation of environmental HCHO. However, due to the increasing trend of the estimated concentrations in Oax, annual HCHO-related cancer risk also showed an increase over the years, so it is considered of great relevance to continue monitoring HCHO in this zone.